How Patent Rights Affect Vietnam‟s Importation - Nguyen, Thi Hoang Oanh (H. : ĐHQGHN, 2018)
Stronger patent rights (PRs) will help innovators to protect their inventions in domestic and export markets, however stronger patent right exporting decisions depend on market expansion and market power effects. Although it is quite late to promulgate patent law, Vietnam began to record patent applications and granted them for both domestic and foreign firms in 1981 (patent law was enacted in 2005). However the number of foreign patent applications is different among Vietnam‟s trade partners. The author used a number of patent applications of Japan, the United States, the United Kingdom, Germany, and France to analyze the relationship between trade inflow from those countries and PRs and have found that Japan applied for the greatest number of patents, which have increased over time. Japanese exports to Vietnam are dominated by market power effects, while other countries‟ patent application numbers tend to fluctuate or increases insignificantly over time, with exports being dominated by market expansion effects.